The Study of Dynamic Processes in the Boiler Furnace with Circulating Fluidized Bed; MATEC Web of Conferences; Vol. 72 : Heat and Mass Transfer in the System of Thermal Modes of Energy – Technical and Technological Equipment (HMTTSC-2016) - Gil A. V. Andrey Vladimirovich (2016, 2016)
Title screen